Avaliação da qualidade dos serviços prestados pela Biblioteca Central da UFES utilizando o método Servqual - Costa, Jhonathan Cavalcante da (2013)
The present paper aims at assessing the service quality provided by the Central Library (CL henceforth) at the Federal University of Espírito Santo (UFES), by using the Servqual method. This research is a case study of quantitative and qualitative nature. The data triangulation was obtained by carrying out a survey with 363 users, an interview with nine librarians, and access was granted to the university’s documents, which describe the Central Library’s basic characteristics. The survey was carried out by using a Servqual scale-based questionnaire in a pre-test administered at the Sectoral Technology Library (BST), at UFES. Two collecting modalities were used in the survey carried out at the CL: in attendance and online. 110 in attendance questionnaires were collected and 253, online. The interviews with the CL employees were based on 116 records of user’s opinions, previously collected at the CL before this research. Besides these documents, advertised institutional information was consulted both in the CL’s service catalogue and on the CL and UFES’s websites. Concerning the services offered by the CL, four dimensions were identified, with negative averages, indicating the necessity of improvement of the services provided. The recommended priority actions to the CL are: a) improve its facilities and equipments; and b) qualify and motivate its workers towards user service. These actions should lead to problem solutions related to studying conditions (lighting, air conditioning, water, restrooms, physical space, furniture and silence) and access to information (internet, self-checkouts, total number of copies, checkout limitations and renewing alerts).